2008
DOI: 10.1074/jbc.m705513200
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Bcr GTPase-activating Domain Is Regulated through Direct Protein/Protein Interaction with the Rho Guanine Nucleotide Dissociation Inhibitor

Abstract: The cycling of Rac GTPases, alternating between an active GTP-and an inactive GDP-bound state, is controlled by guanine nucleotide exchange factors, GTPase-activating proteins (GAPs), and guanine nucleotide dissociation inhibitors (GDIs). Little is known about how these controlling activities are coordinated. Studies using null mutant mice have demonstrated that Bcr and Abr are two physiologically important GAPs for Rac. Here, we report that in the presence of RhoGDI␣, Bcr is unable to convert Rac-GTP to Rac-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
(28 reference statements)
1
20
0
Order By: Relevance
“…Previously, BCR GAP activity was reported to be regulated by direct protein/protein interactions with the Rho guanine nucleotide dissociation inhibitor (Kweon et al, 2008). In the present work, an intramolecular interaction between the N-and C-termini of BCR was enhanced upon dephosphorylation by PTPRT and as a result, we found that BCR GAP activity seemed to be inhibited.…”
Section: Bcr Is a Key Factor In Neuronal Developmentsupporting
confidence: 51%
“…Previously, BCR GAP activity was reported to be regulated by direct protein/protein interactions with the Rho guanine nucleotide dissociation inhibitor (Kweon et al, 2008). In the present work, an intramolecular interaction between the N-and C-termini of BCR was enhanced upon dephosphorylation by PTPRT and as a result, we found that BCR GAP activity seemed to be inhibited.…”
Section: Bcr Is a Key Factor In Neuronal Developmentsupporting
confidence: 51%
“…Ligation of 5Ј SalI-StuI ϩ NaeI-SalI into pSK digested with SalI was followed by isolation of clones in the right orientation, to allow removal of the insert as 5Ј XbaI-3Ј KpnI fragment and ligation into pCDE ϫ XbaI ϫ KpnI. The Xpress-tagged BcrGAP, EGFPBcr, GST fusion BcrGAP, GST fusion AbrGAP, Xpress-tagged Bcr wild type, and Xpress-tagged BcrR1090A mutants have been described previously (8,19). TG2 was also subcloned by PCR into pProEx/HTa for purification of recombinant His 6 -tagged TG2.…”
Section: Methodsmentioning
confidence: 99%
“…GST Pull-down Assay-All procedures were done as described previously (19) with minor modifications. Recombinant GST fusion proteins were purified from Escherichia coli as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations